Remotely controlled electro-responsive on-demand nanotherapy based on amine-modified graphene oxide for synergistic dual drug delivery. (September 2022) - Sahoo, D.; Mitra, T.; Chakraborty, K.; Sarkar, P.
Abstract: This study focuses on the development of a new electric field responsive graphene oxide (GO) nanoparticle system for on-demand drug delivery. Today, GO is an attractive option adopted in various biological applications for its exclusive features such as flexibility, conductiveness, cost-effectiveness, and external stimuli-responsive nature. It is usual to utilize multiple drugs in cancer treatment. This kind of therapy has lesser side-effects, drug resistance, and is more effective than utilizing only one drug. This study aims to determine low-voltage-controlled dual drug (aspirin and doxorubicin) release from GO surface. Here, we have demonstrated how to control the drug release rate remotely with a handy mobile phone, with zero passive release at idle time. In addition, the study focused to estimate the synergism of aspirin with doxorubicin in the release mechanism from GO in the presence of external voltage, using the spectroscopic method. Moreover, we observed aspirin- and doxorubicin-induced synergistic antitumor activity in MDA-MB 231 (breast cancer cell) in vitro . Thus, our study presents a noble combination of aspirin and doxorubicin that could be utilized for remotely controlled on-demand drug delivery for triple negative breast cancer treatment, using GO as a carrier. Graphical abstract: Image 1 Highlights: Synthesis of modified graphene oxide conjugated with hydrophilic (ASP) and hydrophobic drug (DOX) drug. Study the effectiveness of ASP in DOX release from modified graphene oxide in presence of external voltage. Examine as synthesized graphene system for on-demand drug delivery for both ASP and DOX. How the passive release problem from as synthesized dual drug delivery system can be prevented. Execution of cell study to verify the efficacy of the drug release in the presence of the external voltage.